Cognitive Emotional Regulation Questionnaire: a Factorial Validation Study in Spanish for Children (CERQ-k) - Viviana Lemos (Universidad de San Buenaventura, 2021)
Background: The cognitive regulation of emotions is a fundamental variable in socio-affective functioning, being an essential skill in childhood due to its relationship with multiple areas of social functioning. Although there is a version that allows evaluating this construct (CERQ-k), translated and adapted for Argentine children, the structural model found does not fully coincide with the model proposed by the authors of the original version of CERQ. Objective: To test, through Confirmatory Factor Analysis (CFA), the model obtained in the adapted version and compare it with that of the original version of the instrument. Method: From a non-probabilistic sample, 761 children between the ages of 9 and 12, from the provinces of Entre Ríos and Córdoba, participated in the study. Descriptive analyzes of the items, CFA, and reliability analysis were carried out. Results: The CFA indicated an adequate fit in both models, although the second-order model proved to be more parsimonious and with satisfactory fit and error indices. Conclusion: The CERQ-k version adapted to Argentina, whose structure has been confirmed in this study, allows a valid and reliable measure of the construct to evaluate the cognitive regulation of emotion in children aged 9 to 12 years.